Multi-criteria model for prioritizing management actions: case study in a sugar energy industry - Santos, Elenilson Rivando dos (Brazilian Journal of Production Engineering, 2025)
To generate competitive advantage, sugar and ethanol industries seek procedures and technologies that can promote continuous improvements in their processes, especially in logistics management and storage of their products, such as sugar, which is implicitly linked to food safety. Thus, the objective of this work is to propose a multicriteria decision support model aligned with the expectations of logistics management and the activities inherent to the bagging, storage, and distribution of sugar from a plant located in northeastern Brazil. The PROMÉTHÉE method was used to evaluate the problem and order the alternatives according to the decision maker's preferences, thus obtaining a ranking with fifteen positions for the alternatives that would be applied in the industry's logistics management, the first three being: creation of an allergen management system, daily inventory monitoring, and control of sugar specifications. The ordered alternatives began to be applied in the 2022/2023 harvest in the industry, with satisfactory results and good adherence by other sectors.
Keywords: Warehouse; Multicriteria decision; Prométhée